Kinetics of the chromosome 14 microRNA cluster ortholog and its potential role during placental development in the pregnant mare - Pouya Dini; Peter Daels; Shavahn C. Loux; Alejandro Esteller-Vico; Mariano Carossino; Kirsten E. Scoggin; Barry A. Ball (BMC Genomics, 2018)
Abstract Background The human chromosome 14 microRNA cluster (C14MC) is a conserved microRNA (miRNA) cluster across eutherian mammals, reported to play an important role in placental development. However, the expression kinetics and function of this cluster in the mammalian placenta are poorly understood. Here, we evaluated the expression kinetics of the equine C24MC, ortholog to the human C14MC, in the chorioallantoic membrane during the course of gestation. Results We demonstrated that C24MC-associated miRNAs presented a higher expression level during early stages of pregnancy, followed by a decline later in gestation. Evaluation of one member of C24MC (miR-409-3p) by in situ hybridization demonstrated that its cellular localization predominantly involved the chorion and allantoic epithelium and vascular endothelium. Additionally, expression of predicted target transcripts for C24MC-associated miRNAs was evaluated by RNA sequencing. Expression analysis of a subset of predicted mRNA targets showed a negative correlation with C24MC-associated miRNAs expression levels during gestation, suggesting the reciprocal control of these target transcripts by this miRNA cluster. Predicted functional analysis of these target mRNAs indicated enrichment of biological pathways related to embryonic development, endothelial cell migration and angiogenesis. Expression patterns of selected target mRNAs involved in angiogenesis were confirmed by RT-qPCR. Conclusion This is the first report evaluating C24MC kinetics during pregnancy. The findings presented herein suggest that the C24MC may modulate angiogenic transcriptional profiles during placental development in the horse.